Adaptation through the production of siderophore of endophytic bacteria isolated of rice soils and the capacity to grow in the presence of cadmium - Mendoza, Yelitza Aguas; Corderos, Alexander Pérez; Vergara, Donicer E. Montes (Journal of Ecohumanism, 2024)
The objective was to assess the in vitro capacity of siderophore production by Bacillus cereus strain BN5in different concentrations of cadmium (Cd). The bacterium was isolated from the rice variety cultivated in the municipality F2000 Achi-Antioquia, Colombia. Aliquots B. cereus strain BN5 log phase was inoculated into minimal medium tris-MMT with different concentrations of CdCl2. The experiment was incubated with stirring at 150 rpm at 32 ° C / 90 hours; growth of bacteria in each treatment was assessed by turbidimetry technique at 600 nm. Siderophore of production was determined in the medium azurol-S (CAS). There is an inverse relationship between population density and concentration of Cd by tissue, being larger amount of bacteria in panicle compared to other tissues. B. cereus BN5 tolerated up to 500 mg / L of CdCl2 and siderophores produced in the different treatments tested. This endophytic bacteria may be used in the future as an alternative for bioremediation and safe production of rice in soil contaminated with Cd.